2010
DOI: 10.1002/jcb.22737
|View full text |Cite
|
Sign up to set email alerts
|

Activated α2 macroglobulin induces matrix metalloproteinase 9 expression by low‐density lipoprotein receptor‐related protein 1 through MAPK‐ERK1/2 and NF‐κB activation in macrophage‐derived cell lines

Abstract: Macrophages under certain stimuli induce matrix metalloproteinase 9 (MMP-9) expression and protein secretion through the activation of MAPK-ERK and NF-κB signaling pathways. Previously, we demonstrated that activated α(2)-macroglulin (α(2)M*) through the interaction with its receptor low-density lipoprotein receptor-related protein 1 (LRP1) induces macrophage proliferation mediated by the activation of MAPK-ERK1/2. In the present work, we examined whether α(2)M*/LRP1interaction could induce the MMP-9 productio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
40
1

Year Published

2012
2012
2017
2017

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 46 publications
(47 citation statements)
references
References 50 publications
6
40
1
Order By: Relevance
“…It has previously been shown that NF-κB and p38 MAPK play an important role in the regulation of MMP-9 and macrophage migration [11,14]. In the present study, we determined that NF-κB and p38 MAPK activation were markedly increased in RAW264.7 cells in response to LPS stimulation.…”
Section: Resultssupporting
confidence: 61%
See 1 more Smart Citation
“…It has previously been shown that NF-κB and p38 MAPK play an important role in the regulation of MMP-9 and macrophage migration [11,14]. In the present study, we determined that NF-κB and p38 MAPK activation were markedly increased in RAW264.7 cells in response to LPS stimulation.…”
Section: Resultssupporting
confidence: 61%
“…In contrast, signal transducer and activator of transcription 3 (STAT3), a potential anti-inflammatory mediator, can inhibit MMP-9 expression [13]. Other studies have demonstrated that activation of p38 mitogen-activated protein kinase (MAPK) and extracellular regulated protein kinases 1/2 (ERK1/2) up-regulated MMP-9 expression [12,14,15], while JNK (c-Jun N-Terminal kinase) phosphorylation reduced MMP-9 expression [15,16]. Thus, upstream regulators of MMP-9, such as STAT3 and NF-κB, may be utilized as therapeutic targets and can provide new insights into the treatment of many inflammatory diseases.…”
Section: Introductionmentioning
confidence: 99%
“…In particular, various deregulated proteins related to inflammatory status observed in OA have been reported also to play a direct/indirect effect on the enzymatic activity of matrix proteases and on extracellular matrix (ECM) turnover. For example, α2MG (up-regulated in OA - Table 2) modulates MMPs/ ADAMTs activity [56] and its macrophage production [57], plays a distinct role in ECM turnover [58] and is overexpressed in non-infectious equine arthritis [59], human OA, JA and RA [36,38,60]. Similarly, ITI-H1 (up-regulated in OA samples - Table 2) plays a prominent role in HA metabolism, affects the function of various matrix proteins and has been already associated with OA and RA [37,61].…”
Section: Discussionmentioning
confidence: 99%
“…Atherosclerosis. Atherosclerosis is a pathological thickness of artery wall due to fatty acids and cholesterol deposition (Caceres et al, 2010). An early event in the onset of the disease is the altered permeability of the endothelial layer to LDL and fatty acids which then are loaded in the sub-endothelial space (Hansson, 2005).…”
Section: Biological Aspectsmentioning
confidence: 99%